2011
DOI: 10.5741/gems.47.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Ruby and Sapphire from the Tan Huong-Truc Lau Area, Yen Bai Province, Northern Vietnam

Abstract: Primary and secondary deposits in the Tan Huong-Truc Lau area of northern Vietnam's Yen Bai Province have supplied rubies (especially star rubies) and some sapphires-mostly of cabochon quality-for more than a decade. The gems are typically translucent to semitransparent and pink to purplish or brownish red, with rare color zoning. The most distinctive features of this corundum after polishing include growth zoning and asterism. The samples contain relatively high amounts of Fe and variable Ti and Cr. The geolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Rubies from these two Vietnamese sources can be differentiated by their ratios of Cr 2 O 3 /Fe 2 O 3 and Cr 2 O 3 /TiO 3 , both of which are higher in Luc Yen samples (Hauzenberger et al, 2003). A comparative study of the Yen Bai material by one of the authors (Nguyen et al, 2011) indicated lower Cr and higher Fe in ruby from the newer mines. Furthermore, distinctive internal features in ruby and fancy sapphire from the old mines were presented by Kane et al (1991).…”
Section: Ruby and Sapphirementioning
confidence: 98%
See 3 more Smart Citations
“…Rubies from these two Vietnamese sources can be differentiated by their ratios of Cr 2 O 3 /Fe 2 O 3 and Cr 2 O 3 /TiO 3 , both of which are higher in Luc Yen samples (Hauzenberger et al, 2003). A comparative study of the Yen Bai material by one of the authors (Nguyen et al, 2011) indicated lower Cr and higher Fe in ruby from the newer mines. Furthermore, distinctive internal features in ruby and fancy sapphire from the old mines were presented by Kane et al (1991).…”
Section: Ruby and Sapphirementioning
confidence: 98%
“…Supplies of facet-grade ruby from Luc Yen (as well as Quy Chau) have become rare, and cabochon-quality ruby and fancy sapphire are more common (figure 3). One interesting feature of ruby and sapphire from the newer mines is that the crystals are very typically surrounded by spinel, which generally follows the morphology of the underlying corundum crystal (see Nguyen et al, 2011). The boundary between the corundum and the spinel is slightly rounded, suggesting disequilibrium between the two (Häger et al, 2010;Hauzenberger et al, 2010).…”
Section: Ruby and Sapphirementioning
confidence: 99%
See 2 more Smart Citations
“…Ruby may contain Ti, V, Ga in trace amounts together with Cr, Fe. Sapphire synthesizes chromium red, nickel yellow, chromium + nickel pinkish orange while producing titanium and iron blue surface [7,22,23]. Changes in the valance values of the elements Fe, Mg, Ca, Ni in the case of the pink color of the ruby color after heat treatment in the nitrogen atmosphere, the heat regulation of these elements in the crystal structure and the changes in the oxygen vacancies are influential.…”
Section: Figure 2 Uv-vis Spectrometers Of Raw Ruby and Annealed In Nmentioning
confidence: 99%